(untitled) (Stato, Chiese e pluralismo confessionale, 2014)
Il contributo, non sottoposto a valutazione, riproduce il testo integrale, corredato delle note, della relazione al Convegno Nazionale dell’ADEC sul tema “Per una disciplina che cambia. Il diritto canonico e il diritto ecclesiastico nel tempo presente” (Bologna, 7-9 novembre 2013), ed è destinato alla pubblicazione negli Atti. SOMMARIO: 1. Osservazioni introduttive - 2. Il fenomeno religioso nelle costituzioni europee del XXI secolo - 3. La bilateralità con particolare riferimento alla Germania - 4. Osservazioni conclusive. ABSTRACT This essay examines the legal condition of religious denominations in the European States’ new Constitutions. It focuses upon the legal provisions concerning the principle of cooperation and its application contained both in these Constitutions and in the German Länder’s agreements signed with religious denominations after the Reunification. The inconsistencies thereby originated are also taken into account as regards both European legal rules and the condition of religious denominations within national States.